(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article presents the characteristics of modern youth slang, its types and causes are considered. The structure and composition of youth slang are analyzed, and the leading directions of its development are highlighted. The most common types of youth slang are highlighted in detail: school, university, music, gaming, Internet jargon and professional jargon. Special emphasis is placed on the study of the relationship between youth subculture and linguistic innovations.